The Effect of Multilevel Doses of Caffeine on Tissue Macrophage and Blood Lymphocyte Count in Autologous Full Thickness Skin Graft Healing in Sprague Dawley Rats - Wahyu Haris Prabowo; Awal Prasetyo; Neni Susilaningsih (HM Publisher, 2022)
Backgrounds. A skin graft is one of the routine surgical procedures performed. This procedure gives excellent results when done as early as possible after the trauma. Caffeine has a mechanism as an adenosine-receptor A2 antagonist which can induce wound healing through increased angiogenesis. This study aimed to determine the efficacy of coffee caffeine in the initiation of full thickness skin graft autologous wound healing by assessing the number of macrophages and lymphocytes in Sprague-Dawley rats. Methods. The research design is an experimental study with a post-test-only approach with a control group design. Twenty male Sprague Dawley rats aged 15 weeks (140 – 150 grams) were randomly divided into four groups. One group became the control group (decaffeinated) while the other group received various doses of caffeine (3 mg/kgBW, 6 mg/kgBW, and 9 mg/kgBW). Autologous skin grafts were performed in all groups. HE examination was performed to confirm the number of macrophage cells in the tissue. Data analysis was carried out with the help of SPSS 25 software. Results. There were significant differences in the number of tissue macrophages in the four groups. The group that received 9 mg/kgBW of caffeine showed the highest number of macrophages compared to the other groups. Based on the number of lymphocytes in the peripheral blood, the group that received a dose of 6 mg/kg BW showed the highest number of lymphocytes compared to other groups. Conclusion. Caffeine showed the ability to initiate full thickness skin graft autologous wound healing by increasing the number of macrophages and lymphocytes in Sprague Dawley rats.